Antibacterial effect of Nordic berries against urinary tract infection causing E. coli strains - Tuuli Aro; Stefan Martens; Hely Häggman; Mysore V. Tejesvi (2019)
Wild berry species at northern latitudes contain many bioactive compounds beneficial for human health, making them appealing sources for natural antimicrobial agents, for example against urinary tract infection (UTI). The present study aims to evaluate the antibacterial impact of bilberry (Vaccinium myrtillus L.), lingonberry (Vaccinium vitis-idaea) and crowberry (Empetrum nigrum) against clinical E. coli strains from UTI patients and against common bacterial pathogens. To accomplish this aim, clinical E. coli strain, E. coli, K. pneumonia, S. aureus and P. aeruginosa strains were predisposed to berry extracts to assess inhibition halos (RDA), growth inhibition kinetics (GIK) and minimal inhibition concentrations (MIC). Water, acetone and ethanol were used in extraction step to evaluate if the chosen solvent have an impact on the antibacterial effect or secondary metabolite content of extracts. Lastly, the secondary metabolic spectra of berry extracts were investigated. All berry extracts showed antibacterial activity irrespective of the extraction method; bilberry (RDA: 4-14 mm, MIC: 3.125-100) lingonberry (RDA: 6-10.5 mm, MIC: 12.5-50) and crowberry (RDA: 3-11 mm, MIC: 6.25 - 50). The selected solvent in extraction step altered the bacterial growth inhibition potential of the extract, which might be due to the found differences in secondary metabolite quantities between each berry extracts. The results suggest that bilberry, lingonberry and crowberry have antibacterial properties against UTI pathogen E. coli and other common infectious bacteria. Also, solvent selection in the extraction step altered the antibacterial effect and secondary metabolite content of berry extracts, indicating the need of standardized antibacterial assay for plant-based products.